: Kajian Hak Perempuan Timur Tengah dalam Perspektif Ekonomi Politik Media - Gerson Ralph Manuel Kho; Teguh Hidayatul Rachmad; Yohanes Probo Dwi Sasongko; Sara Hasan (Jurnal Spektrum Komunikasi, 2023)
The Middle Eastern media generally promotes the dignity of women more. The issues facing women who have endured conflict or sexual assault are constantly brought up in the news and widely distributed through movies. Discourse based on media culture demonstrates how firmly the Middle East supports the rights and dignity of women. The desire of the media to demonstrate the strength and might of a nation, a person, or a viewpoint is directly tied to the political and economic interests of this. Power relations are actually depicted in Middle Eastern media by a culture that has evolved from generation to generation. Unlike before the movement to uphold women’s rights, men's right to express their masculinity is now limited. This is the state of the art in scientific writings that take a media, political economy, and history approach to studying Middle Eastern media culture. Researchers in Indonesia still hardly ever use qualitative research methodologies that take a media political economy perspective with four units of analysis, including history, social totality, morality, and praxis orientation, that are connected to media cultures outside of Indonesia (the Middle East). The goal of this study was to determine the Middle Eastern countries' power structures based on their publicized media cultures. The Middle East is particularly receptive to industrialization that helps women, as shown by historical characteristics of the region that produce films and news about women's fights that women always win over males. Furthermore, the Middle East is home to a large number of female political figures, demonstrating that the media's political economy interests in promoting women are upheld there.